The Role of Religion on the Health Practices of Mexican Americans - Lujan, Josefina (Journal of religion and health, 2006)
Twenty million Mexican Americans live in the U.S. (U.S. Census 2000 File, 2000). It is vital that health care clinicians become familiar with and acknowledge the role of religion or religiosity on the health practices of Mexican Americans so that these needs may be addressed through holistic care. This paper reviews the origin and role that religion plays in the health practices of Mexican Americans. The potential benefits of addressing these client's religious needs are examined and suggestions are offered on how health care clinicians may address these needs in a culturally sensitive manner.